Multidimensional comparative analysis of the number of deaths in Europe between 2018-2021 in terms of economic security - Kozicki, Bartosz; Grabowska, Sabina; Ovsepyan, Arsen; Sowa, Bogdan (Polityka i Społeczeństwo, 2022)
The study concerned a multidimensional comparative analysis of the number of deaths in 30 European countries between 2018-2021, also by age groups and type of vaccination in Poland in 2021 in terms of the impact of the COVID-19 pandemic and economic security. The data for the research was obtained from the websites of Eurostat and the Central Statistical Office. They were grouped and sorted from largest to smallest. In order to achieve the aim of the study, the death indices were calculated and analyzed. The obtained test results are included in bar charts. The article ends with a summary and final conclusions.